W-boson production in the high energy electron-photon collisions - Shershan, Ivan A.; Shishkina, Tatiana V. (Journal of the Belarusian State University. Physics, 2019)
In this paper the analysis of W-boson production process in high-energy electron-photon collisions as a tool to search for deviations from the Standard Model is considered. In particular, a set of extended gauge models, including anomalous multi-boson interactions, are discussed as a promising way for «new physics» study. A numerical analysis of the total cross sections of the processes was carried out. The lowest order radiative corrections in the soft-photon approximation within the Standard Model are taken into account. Calculations beyond the Standard Model was performed, the kinematic  features of the cross sections were identified. The restrictions on the anomalous triple gauge boson coupling constants were analyzed and the kinematic areas to the search for their manifestations were obtained during the experiments at the  International Linear Collider. The paper shows that the search for «new physics» effects based on electron-photon  collisions around the W-boson production peak is the maximal promising. It was also shown that future experiments at high luminosity linear colliders will significantly clarify the constraints on anomalous gauge coupling constants.
Keywords: cross section; «new physics»; Standard Model; International Linear Collider